Disharmony of Parents and Children in an Online Learning during the Covid-19 Pandemic in Indonesia - Fitri Oviyanti; Hasse Jubba; Zuhdiyah Zuhdiyah (Nadwa: Jurnal Pendidikan Islam, 2021)
The disharmony of parents and children in online learning during the pandemic was a crucial phenomenon. This disharmony had caused difficulties for children to improve their learning motivation. In line with that, this study not only mapped out the forms of disharmony between parents and children in online learning but also analyzed the causes behind disharmony and its implications for children’s learning motivation. The data of this study was collected based on interviews with three different groups of informants by taking into account the structural characteristics of the groups. The results of this study showed that the emotional pressure, inability, and unpreparedness of parents and children in dealing with changes in learning traditions during the pandemic had strengthened the disharmony between them. The disharmony had a consequence on the decline in children’s learning motivation in online learning during the Covid-19 pandemic. The inability and unpreparedness of parents to accompany their children in online learning throughout the pandemic were crucial factors that caused disharmony. This study suggested the need to expand the cases studied and added data sources to enable understanding of the impact of the Covid-19 pandemic on the disharmony of parents and children.